Suplementação mineral e energética para novilhas de corte em pastagens cultivadas - Rosa, Vanessa Bayer da (2022)
Knowledge of the importance of the use of winter and summer cultivated pastures and mineral supplementation for beef heifers is essential for the development of precision livestock. Body and reproductive development of heifers supplemented with energetic mineral salt and common salt in annual ryegrass (Lolium multiflorum Lam.) followed by millet pasture (Pennissetum americanum Leeke) was evaluated. Beef heifers have high body performance when using annual ryegrass and then millet, regardless of the type of mineral supplement provided. The forage from annual ryegrass and millet is considered high quality and meets the nutritional requirements of beef heifers, without the need for additional supplementation. Energy mineral supplementation or the supply of common salt do not interfere in the anticipation of mating of beef heifers recreated in cultivated grassland of annual ryegrass and millet. Heifers that have at least 40% of adult body weight in weaning and are recreated in annual ryegrass and millet reach adequate weight to be mated at 18 months of age.